Pengaruh Model Problem Based Learning Terhadap Kemampuan Menganalisis Teks Eksplanasi pada Siswa Kelas VIII Sekolah Menengah Pertama Negeri 1 Kabandungan Tahun Ajaran 2024/2025 - Priadi, Ismat; Supendi, Deden Ahmad; Firdaus, Asep (Universitas Islam Sumatera Utara, 2025)
The low analytical ability of students in understanding explanatory texts at Sekolah Menengah Pertama Negeri 1 Kabandungan serves as the background of this study, which stems from the predominant use of lecture-based teaching methods that fail to actively involve learners in the learning process. This research aims to investigate the effect of the Problem-Based Learning (PBL) model on enhancing students’ ability to analyze explanatory texts in Grade VIII. Employing a quantitative approach with a quasi-experimental design, the study involved two groups: an experimental class receiving PBL-based instruction and a control class taught through conventional methods. Data were collected using a post-test consisting of multiple-choice questions and analyzed through a t-test to determine significant differences between groups. The findings revealed that students taught with the PBL model achieved higher mean scores compared to those in the control class, indicating a statistically significant improvement. Therefore, the implementation of the Problem-Based Learning model demonstrates a positive and significant influence in fostering students’ analytical skills in processing explanatory texts effectively.